Global Impacts Dataset of Invasive Alien Species (GIDIAS) - Sven Bacher; Ellen Ryan-Colton; Mario Coiro; Phillip Cassey; Bella S. Galil; Martin A. Nuñez; Michael Ansong; Katharina Dehnen-Schmutz; Georgi Fayvush; Romina D. Fernandez; Ankila J. Hiremath; Makihiko Ikegami; et al. (Scientific Data)
Abstract Invasive alien species are a major driver of global change, impacting biodiversity, ecosystem services, and human livelihoods. To document these impacts, we present the Global Impacts Dataset of Invasive Alien Species (GIDIAS), a dataset on the positive, negative and neutral impacts of invasive alien species on nature, nature’s contributions to people, and good quality of life. This dataset arises from the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services’ (IPBES) thematic assessment report of this topic. Data were compiled from published sources, including grey literature, reporting a direct observation of an invasive alien species’ impact. All impact records contain up to 52 fields of contextual information and attempt to link impacts to the global standard “environmental impact classification for alien taxa” (EICAT) and “socio-economic impact classification for alien taxa” (SEICAT). GIDIAS includes more than 22000 records of impacts caused by 3353 invasive alien species (plants, vertebrates, invertebrates, microorganisms) from all continents and realms (terrestrial, freshwater, marine), extracted from over 6700 sources. We intend GIDIAS to be a global resource for investigating and managing the variety of impacts of invasive alien species across taxa and regions.